Clinical Characteristics and Patient Outcomes of Urolithiasis and Ureteral Stones in a Pediatric Population - Illahi Bux Brohi, Imran Ali Bajwa, Farhan Ali, Sabieh Ahmad, Hamza Sohail, Tahir Shahzad Nawaz Babar, Aymen Rashid, Dawood Yousuf, Bilal Afzal (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: This study was aimed to highlight the clinical characteristics and patient outcome associated with urolithiasis and ureteral stones in a pediatric urological department. Methodology: A descriptive study was conducted between February 2021 and April 2022 at Gambat Medical Hospital, Khairpur, Sindh. All patients between the ages of 2 years and 17 years presented at the outpatients department and inpatients department for the management of urolithiasis were included in the study. All patients with congenital renal abnormalities were excluded from the study. Sociodemographic and clinical characteristics, treatment/management offered, outcome, and early postoperative complications were documented. All data was analyzed using SPSS version 24. Results: During the study period of one year, a total of 72 pediatric patients were diagnosed with urolithiasis. A mean age of 8.33 (5.6) years was noted with 26 (36.1%) female patients and 46 (63.8%) male patients. 20 (27.8%) patients had left renal stones. Two of these patients had right ureteral stones as well. These patients were managed with right ureterolithotomy and double J-stent placement. There were ten patients with bilateral renal stones. Two patients with a right vesicoureteric junction (VUJ) stone were treated with ureteroscopy (URS). In six (8.3%) cases, residual stones were noted. Conclusion: The majority of the pediatric population had solitary right renal stones and the most common procedure performed at our centre was pyelolithotomy followed by nephrectomy. The majority had a good postoperative outcome. Keywords: Renal Colic, Pyelolithotomy, Percutaneous Nephrolithotomy (PCNL), PUJO, J-stent placement